SCIENTIFIC ORGANIZATION AND LABOR PROTECTION AS A BASIS OF ECONOMIC MODEL EFFICIENCY - I. N. Merzlikin; O. G. Feoktistova; T. G. Feoktistova (Научный вестник МГТУ ГА, 2016)
In the context of today’s economic situation in our country and the ways that are planned to improve it, it has been offered to recall the problem of scientific labor organization (NOTES) that makes it possible to provide an increase in economic efficiency of production without considerable extra capital expenditures.The idea of article is to consider the factors at overcoming of which the application of scientific labor organization is aimed and to draw attention to the ways of solving labor protection tasks that emerge in labor process.